Efficacy and Safety of Alteplase Combined with Urinarykallid for Intravenous Thrombolysis on Acute Cerebral Infarction - Jiahui Shao; Bao, Linyi; Jin, Xinchun; Jin, Haimiao; Chen, Yun (Neurochemical journal, 2024)
This study aimed to explore the efficacy and safety of alteplase combined with urinarykallid for the intravenous thrombolysis of patients with acute cerebral infarction. Patients ( n = 125) who were admitted to our hospital were included and divided into Group A ( n = 60) and Group B ( n = 65). Patients in Group A were treated with alteplase for intravenous thrombolysis, based on which urinarykallid was administered to patients in Group B as a combination treatment. Compared to Group A, Group B was significantly lower in hs-CRP and TNF-α levels ( p < 0.001), total incidence of adverse reactions ( p < 0.05), and NIHSS score ( p < 0.001) and higher in IL-10 level ( p < 0.001), total effective rate (markedly effective + effective/total cases × 100%. Compared to the single administration of alteplase, the combination of alteplase and urinarykallid for the intravenous thrombolysis of patients with acute cerebral infarction can achieve better efficacy at a lower incidence of adverse reactions and play a more significant role in clinical treatment.